Two new Japanese species of Gastrotricha (Chaetonotida, Chaetonotidae, Lepidodermella and Dichaeturidae, Dichaetura), with Comments on the Diversity of Gastrotrichs in Rice Paddies - Suzuki, Takahito G.; Maeda, Masako; Furuya, Hidetaka (Zootaxa, 2013)
Two new species of freshwater gastrotrichs are described from rice paddies in Otsu, Shiga, Japan. Lepidodermella acantholepida n. sp. is a medium sized species attaining a length of 145 μm, scales are flattened ovals and similar to those of L. squamata except that two dorsal scales near the furca have a claw-like spine. Dichaetura filispina n. sp. is a medium sized species attaining a length of 185 μm, characterized by a thin, fiber-like spine, a spined furca with a constriction near its base and an elongate body. A total of 44 species (seven genera) including two new species were found in the rice paddies. The diversity of rice paddy gastrotrichs is briefly discussed.